Madura Academics on Qur’anic Createdness and Foundations of Islamic Language Philosophy - Damyati, Akhmad Rofii; Ludfi; Hisam, Mohammad Ali; Syatila, Nawal (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
The debate over the creation of the Qur’an (khalq al-Qur’an) is one of the most influential controversies in the history of Islamic theology. Traditionally understood as a doctrinal dispute over divine attributes, this debate also raises deeper questions about the relationship between divine meaning and human language. However, the linguistic dimension of this debate is rarely systematically examined in contemporary science. Therefore, this study aims to reinterpret the khalq al-Qur’an debate as a discourse that reflects the conceptual understanding of different languages in the Islamic theological tradition. This study uses a qualitative theoretical design using conceptual analysis and rational reconstruction. The classical theological texts of Mu’tazilah, Ash’ariyyah, and Hanabilah are analyzed to identify key concepts related to divine utterance. In addition, empirical data was collected through interviews with contemporary Islamic scholars to provide a contextual perspective on the debate. The findings suggest that these theological schools represent three different conceptual models of language. Mu’tazilah views divine utterance as a temporal communicative act, Ash’ariyyah distinguishes between eternal meaning (kalam nafsi) and temporal linguistic expression (kalam lafẓi), and Hanabilah emphasizes the authority of the revealed text. This study concludes that the debate on the khalq al-Qur’an contains conceptual insights that can be reconstructed as a discourse on the ontology of language in the Islamic intellectual tradition.